2020
DOI: 10.1186/s12889-020-08989-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human alveolar echinococcosis in China: a systematic review and meta-analysis

Abstract: Background: Human alveolar echinococcosis (HAE), caused by the larvae of Echinococcus multilocularis, is a severe parasitic disease that is a major public health concern. New HAE cases in China account for 91% of the global HAE burden every year. Although there are a few studies and systematic reviews (SRs) on the prevalence of HAE in China, trends in the prevalence have not been estimated. This study aims to describe the overall variation in the trend of HAE prevalence in China, and provide evidence for preve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
11
2
Order By: Relevance
“…The pooled prevalence of AE and CE were 2.34% (95% CI: 1.74–3.13%) and 4.45% (95% CI: 2.53–7.71%), respectively, in the included individuals. However, the prevalence of AE was significantly higher than that previously calculated in China (0.96%) ( 3 ). Since we aim at understanding the risk factors for AE and CE, several studies on prevalence were not included due to restrictions in the search terms (i.e., “risk factor”), which could partially explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The pooled prevalence of AE and CE were 2.34% (95% CI: 1.74–3.13%) and 4.45% (95% CI: 2.53–7.71%), respectively, in the included individuals. However, the prevalence of AE was significantly higher than that previously calculated in China (0.96%) ( 3 ). Since we aim at understanding the risk factors for AE and CE, several studies on prevalence were not included due to restrictions in the search terms (i.e., “risk factor”), which could partially explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 75%
“…Cystic echinococcosis (CE) and alveolar echinococcosis (AE) are the two most common forms of human echinococcosis and are caused by the larval stages of Echinococcus granulosus and Echinococcus multilocularis , respectively ( 1 ). Dogs are the usual definitive host of E. granulosus ( 2 ), whereas dogs and foxes are the main definitive hosts of E. multilocularis ( 3 ). Both are transmitted by the fecal-oral route through contact with infected definitive hosts or with food or water contaminated with E. granulosus or E. multilocularis eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with cystic echinococcosis (CE), HAE is by far more severe in affected patients. Despite the marked healthcare improvements in the western agricultural and pastoral regions of China, and the rising national health examination rates, the early detection rates of HAE cases continue to rise at an alarming rate [ 21 , 22 ]. In the past, radical resection surgery was the first choice for patients with HAE [ 23 ]; however, with early diagnosis of lesions and the progress of treatment, choosing the treatment with less trauma and fewer complications can better reflect the humanistic care for the patients [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…AE is endemic in certain parts of the world, especially in Europe, Northern America, and Central Asia (Deplazes et al, 2017). A recent meta-analysis indicated that the pooled prevalence of AE in China was 0.96% (Wang et al, 2020). In China, the AE endemic area is restricted to the northwest region (Qian et al, 2017), for example, Qinghai province and Gansu province.…”
Section: Discussionmentioning
confidence: 99%